A Comparison of Fecal Immunochemical and High‐Sensitivity Guaiac Tests for Colorectal Cancer Screening. (November 2017) - Shapiro, Jean A; Bobo, Janet K; Church, Timothy R; Rex, Douglas K; Chovnick, Gary; Thompson, Trevor D; Zauber, Ann G; Lieberman, David; Levin, Theodore R; Joseph, Djenaba A; Nadel, Marion R
Abstract : Objectives: Annual testing using either a high‐sensitivity guaiac fecal occult blood test (HS‐gFOBT) or a fecal immunochemical test (FIT) is recommended for screening average‐risk people for colorectal cancer. We compared the performance characteristics of the HS‐gFOBT Hemoccult II SENSA and two FITs (InSure FIT and OC FIT‐CHEK) for detecting advanced colorectal neoplasia. Methods: The study included 1, 006 asymptomatic patients, aged 50–75 years, who were scheduled to receive a screening colonoscopy at gastroenterology practices in the Minneapolis and Indianapolis metropolitan areas. Each participant was asked to complete all three stool tests before their colonoscopy. Each test's performance characteristics were evaluated using the screening colonoscopic results as the reference standard. Results: Sensitivity for detecting advanced colorectal neoplasia was highest for InSure FIT (26.3%, 95% confidence interval (CI) 15.9–40.7), followed by OC FIT‐CHEK (15.1%, 95% CI 6.7–26.1) and Hemoccult II SENSA (7.4%, 95% CI 1.9–17.0). InSure FIT was statistically significantly more sensitive than both OC FIT‐CHEK (absolute difference in sensitivity=11.2%, 95% CI 0.4–24.2) and Hemoccult II SENSA (difference in sensitivity=18.9%, 95% CI 10.2–32.6). Specificities were relatively high for all tests (between 96.8% and 98.6%). Conclusions: Our results suggest that some FITs are more sensitive than the HS‐gFOBT Hemoccult II SENSA, but these results need to be confirmed in larger asymptomatic populations. Comparisons between the FITs examined in this study and other FITs are needed to determine the best tests for population screening.